Impact of the Belt and Road Initiative on Economic-Social-Natural Ecological Niches and Their Coupling Coordination: Evidence From 11 Countries Along the Route - Cao, Ying; Jiang, Anyin; Cao, Zijian; Fayyaz, Ahmad; Li, Jing; Chen, Weiqiang; Guo, Wenjun (Frontiers in Environmental Science, 2022)
The Belt and Road Initiative (BRI) significantly contributes to the world economy. However, the central part of the Belt and Road (B&R) is located in fragile ecological zones that are arid, semi-arid, or sub-humid. Using the entropy method, the economic-social-natural ecological niches and their coupling coordination during 2008–2019 along B&R’s 11 countries were explored along with regional differences and spatiotemporal characteristics. The economic-social-natural ecological niches were low, with a fluctuating upward trend. Additionally, the average annual growth rate of the synthesis ecological niche dramatically improved after the BRI. Further, the BRI facilitated inter-country trade and promoted the economic ecological niche. However, the BRI marginally affected the social ecological position, possibly because the social ecological niche was high pre-BRI. The natural ecological niche showed a negative growth after the BRI. Further, the coupling coordination of economic-social ecological niche and natural ecological niche showed an upward trend, transforming from severe discoordination to advanced coordination. Although BRI promoted advanced coordination, it did not affect internal categories. Policy recommendations for sustainable development in China-ASEAN Free Trade Area were provided. This study can assist policymakers to balance economic-social development and environmental protection.